Living treasures of Japan - Buch, Miriam; Kane, Dennis B.; Skinner, Thomas (National Geographic Society special, 1980)
Profiles nine artisans and performing artists who are recognized by law as holders of important intangible cultural properties and teaching their artistry to apprentices. Pays visits to a potter, doll sculptor, puppeteer, papermaker, koto musician, swordmaker, textile weaver and dyer, kabuki theater actor and bellmaker.